Novel H16N3 avian influenza viruses isolated from migratory gulls in China in 2023 - Peng, Peng; Shen, Jinyan; Shi, Wenjun; Guo, Jing; Wang, Mengjing; Li, Wenxi; Yue, Zhiqin; Sun, Xiaohong; Guan, Mengdi; Liu, Lili; Xu, Hongke; Xie, Yujiao; et al. (Frontiers in Microbiology, 2025)
As a rare subtype of avian influenza virus, H16 viruses are predominant in gulls but rarely found in domestic birds. The low prevalence of H16 viruses has limited our understanding of their epidemiology and evolutionary dynamics. In this study, we isolated three novel H16N3 viruses from migratory gulls in East Asian–Australasian Flyway in eastern China in 2023, which are significantly different from previously identified isolates. To fully understand the epidemiology and genetics characteristics of the global H16 viruses, we compared the host divergence of several rare subtypes and determined that the H13 and H16 subtypes were predominantly pooled into different species of gulls by sharing their internal genes, whereas the waterfowl of Anatidae served as the primary natural reservoirs of the H8, H11, H12, H14, and H15 subtypes. Detailed phylogenetic analysis revealed the evolutionary divergence of globally circulating H16 viruses and their frequent gene reassortment. Furthermore, the gull origin H13 and H16 viruses collectively served as gene donors for the newly emerged highly pathogenic clade 2.3.4.4b H5N1 viruses because the H13/H16-like PA, NP, and NS genes have been introduced into circulating H5N1 viruses since May 2022 in Europe. To date, the H5N1 reassortants containing the H13/H16-like gene segments have been detected in wild and domestic birds and resulted in mammal and human infections. These results improve our knowledge of the ecology and genetics of H16 viruses and emphasize the need for surveillance to monitor the emergence of novel avian influenza viruses in migratory birds.